Solid electrolyte and method for manufacturing the same

By controlling the crystal structure and diffraction peak separation of solid electrolytes of lithium, phosphorus, sulfur and bromine elements, the problem of hydrogen sulfide generation in low dew point environments is solved, and high lithium ion conductivity and battery safety are improved.

CN116940996BActive Publication Date: 2025-07-18MITSUI MINING & SMELTING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202280017659.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-11
Filing Date
2022-02-28
Publication Date
2025-07-18
Estimated Expiration
2042-02-28

AI Technical Summary

Technical Problem

Existing sulfide solid electrolytes are prone to hydrogen sulfide in low dew point environments, affecting the safety and stability of the battery.

Method used

A solid electrolyte containing lithium, phosphorus, sulfur and bromine elements is adopted, and has a sulfur-silver germanium ore-type crystal structure. The peak A is separated into peak A1 and peak A2 through waveform separation operations in the X-ray diffraction pattern, controlling the peak intensity and half-height-width ratio, ensuring high lithium ion conductivity and inhibiting the production of hydrogen sulfide.

Benefits of technology

It effectively inhibits the production of hydrogen sulfide, improves lithium ion conductivity, and improves the safety and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116940996B_ABST
    Figure CN116940996B_ABST
Patent Text Reader

Abstract

The solid electrolyte contains Li, P, S, and a halogen. The halogen contains at least Br. The solid electrolyte contains a crystal phase having a thiogermanate crystal structure. In an X-ray diffraction pattern measured by an X-ray diffractometer (XRD) using CuKα1 as the radiation source, the solid electrolyte has a peak A in the range of 2θ = 25.2 ± 1.0°. The peak A is separated into two peaks, peak A1 and peak A2, by a waveform separation operation. Let the intensity of peak A1 be I A1 , and the intensity of peak A2 be I A2 . When I A2 / I A1 is 0.37 or more. Let the full width at half maximum of peak A1 be W A1 , and the full width at half maximum of peak A2 be W A2 . When W A2 / W A1 is 3.2 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid electrolyte and a method for manufacturing the same. Further, the present invention relates to an electrode mixture, a solid electrolyte layer, and a battery including the solid electrolyte. Background Art

[0002] In recent years, solid electrolytes have attracted attention as alternatives to electrolytes used in many liquid batteries. A solid-state battery using a solid electrolyte is expected to be put into practical use as a battery having higher safety and higher energy density than a liquid battery using a flammable organic solvent. As the solid electrolyte, for example, a sulfide solid electrolyte containing lithium (Li) element, phosphorus (P) element, sulfur (S) element, and halogen element has been proposed (Patent Documents 1 and 2).

[0003] Prior Art Documents

[0004] Patent Documents

[0005] Patent Document 1: US2016 / 156064A1

[0006] Patent Document 2: US2019 / 148769A1 Summary of the Invention

[0007] Hydrogen sulfide may be generated in a sulfide solid electrolyte in a low dew point environment such as a dry room, for example.

[0008] Therefore, an object of the present invention is to provide a solid electrolyte that suppresses the generation of hydrogen sulfide.

[0009] The present invention provides a solid electrolyte containing lithium (Li) element, phosphorus (P) element, sulfur (S) element, and halogen (X) element,

[0010] wherein the halogen (X) element contains at least bromine (Br) element,

[0011] the solid electrolyte contains a crystal phase having a thiogermanate-type crystal structure,

[0012] the solid electrolyte has a peak A in the range of 2θ = 25.2 ± 1.0° in an X-ray diffraction pattern measured by an X-ray diffraction apparatus (XRD) using Cukα1 as a radiation source,

[0013] by separating the peak A into two peaks, peak A1 and peak A2, by a waveform separation operation, and setting the intensity of the peak A1 as I A1 and the intensity of the peak A2 as I A2 when, the I A2 relative to the I A1 the ratio of (I A2 / I A1)is 0.37 or more,

[0014] Let the full width at half maximum of the peak A1 be W A1 and the full width at half maximum of the peak A2 be W A2 At this time, the W A2 The ratio of W A1 (W A2 / W A1 )is 3.2 or more. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is a flowchart of the waveform separation operation of the diffraction peak.

[0016] Figure 2 is a diagram showing the result of the waveform separation operation of the diffraction peak of the solid electrolyte obtained in Example 1. DETAILED DESCRIPTION OF THE INVENTION

[0017] The present invention will be described below based on preferred embodiments. The solid electrolyte of the present invention is composed of a crystalline substance containing a crystal phase having an argyrodite crystal structure. The argyrodite crystal structure refers to a crystal structure of a compound group derived from the mineral represented by the chemical formula Ag8GeS6. The solid electrolyte of the present invention has a crystal phase having an argyrodite crystal structure, whereby the lithium ion conductivity of the solid electrolyte is improved, and thus it is preferred. Whether the solid electrolyte of the present invention has a crystal phase having an argyrodite crystal structure can be confirmed by measurement based on an X-ray diffractometer (XRD) or the like.

[0018] On the basis of containing a crystal phase having an argyrodite crystal structure, the solid electrolyte of the present invention contains, as constituent elements, a lithium (Li) element, a phosphorus (P) element, a sulfur (S) element, and a halogen (X) element. The X-ray diffraction pattern of the crystal phase derived from the argyrodite crystal structure varies depending on the composition of the crystal phase. When the solid electrolyte of the present invention contains the above elements, in the X-ray diffraction pattern measured by XRD using Cukα1 as the radiation source, in the range of 2θ = 25.2 ± 1.0°, there is a characteristic peak A of the crystal phase derived from the argyrodite crystal structure.

[0019] In addition to this peak A, the solid electrolyte of the present invention sometimes shows peaks in the ranges of 2θ = 15.3° ± 1.0°, 17.7° ± 1.0°, 30.0° ± 1.0°, 30.9° ± 1.0°, and 44.3° ± 1.0°.

[0020] Furthermore, depending on the composition of the elements constituting the solid electrolyte of the present invention, in addition to the aforementioned diffraction peaks, peaks may also be exhibited in the ranges of 2θ = 47.2° ± 1.0°, 51.7° ± 1.0°, 58.3° ± 1.0°, 60.7° ± 1.0°, 61.5° ± 1.0°, 70.4° ± 1.0°, and 72.6° ± 1.0°.

[0021] Peaks derived from an argyrodite crystal structure can be identified using, for example, data with PDF number 00 - 034 - 0688.

[0022] In the present invention, from the perspective of maintaining high lithium - ion conductivity and effectively suppressing the generation of hydrogen sulfide, when peak A observed in the range of 2θ = 25.2 ± 1.0° is separated into two peaks, peak A1 and peak A2, by a waveform separation operation, peak A1 and peak A2 preferably satisfy the relationship described below. It should be noted that the reason for selecting the diffraction peak observed in the range of 2θ = 25.2 ± 1.0° as the target diffraction peak is that in this range, it is not easily affected by diffraction peaks of impurities, and peak separation can be accurately achieved.

[0023] Separating peak A into peak A1 and peak A2 by performing a waveform separation operation on the aforementioned peak A means that the solid electrolyte of the present invention contains other crystal phases in addition to the crystal phase of the argyrodite crystal structure. In the solid electrolyte of the present invention, the crystal phase of the argyrodite crystal structure is preferably the main phase. In the present invention, among peak A1 and peak A2, the peak with relatively high intensity is peak A1 derived from the crystal phase of the argyrodite crystal structure. On the other hand, the peak with relatively low intensity is peak A2 derived from other crystal phases other than the crystal phase of the argyrodite crystal structure. The degree of existence of other crystal phases in the solid electrolyte of the present invention can be evaluated by peak intensity and full width at half maximum.

[0024] Regarding the peak intensity, the larger the ratio of the intensity of peak A2 to the intensity of peak A1, the greater the proportion of other crystal phases can be judged to be.

[0025] Regarding the full width at half maximum, the larger the ratio of the full width at half maximum of peak A2 to the full width at half maximum of peak A1, the lower the crystallinity of other crystal phases can be judged to be.

[0026] It should be noted that the above - mentioned "main phase" refers to the phase with the largest proportion relative to the total amount of all crystal phases constituting the solid electrolyte. Therefore, relative to all crystal phases constituting the solid electrolyte, the content ratio of the crystal phase of the argyrodite crystal structure contained in the solid electrolyte is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and even more preferably 90% by mass or more. The ratio of crystal phases can be confirmed by, for example, XRD.

[0027] Regarding the intensities of peak A1 and peak A2, it is preferable to satisfy the following formula (1).

[0028] I A2 / I A1 ≥0.37 (1)

[0029] In formula (1), I A1 represents the peak intensity of peak A1, and I A2 represents the peak intensity of peak A2. In this specification, the peak intensity refers to the peak height measured from the baseline in the XRD diffraction pattern. I A2 The ratio of I A1 to I A2 / I A1 ) that satisfies formula (1) for the solid electrolyte exhibits high lithium ion conductivity and can effectively suppress the generation of hydrogen sulfide. From the perspective of making this advantage more significant, the value of I A2 / I A1 is more preferably 0.40 or more, and further preferably 0.43 or more.

[0030] From the perspective of maintaining the effect of suppressing the generation of hydrogen sulfide and ensuring lithium ion conductivity sufficient to function as a solid electrolyte, the value of I A2 / I A1 is preferably I A2 / I A1 ≤1.40. From the perspective of making this advantage more significant, the value of I A2 / I A1 is more preferably 1.00 or less, and further preferably 0.60 or less.

[0031] Regarding the full width at half maximum of peak A1 and peak A2, it is preferable to satisfy the following formula (2).

[0032] W A2 / W A1 ≥3.2 (2)

[0033] In formula (2), W A1 represents the full width at half maximum of peak A1, and W A2 represents the full width at half maximum of peak A2. W A2 The ratio of W A1 to W A2 / W A1 ) that satisfies formula (2) for the solid electrolyte exhibits high lithium ion conductivity and can effectively suppress the generation of hydrogen sulfide. From the perspective of making this advantage more significant, the value of W A2 / W A1 is more preferably 3.4 or more, and further preferably 3.6 or more.

[0034] Regarding other crystal structures that are the source of peak A2, from the perspective of ensuring lithium ion conductivity sufficient to function as a solid electrolyte, W A2 / W A1 The value of is preferably W A2 / W A1 ≤ 15.0. From the perspective of making this advantage more prominent, W A2 / W A1 The value of is more preferably 10.0 or less, and even more preferably 7.0 or less.

[0035] Both peak A1 and peak A2 are observed at positions where 2θ = 25.2 ± 1.0°. The positions of the peaks of peak A1 and the peaks of peak A2 are approximately at the same position. From the perspective of maintaining high lithium ion conductivity and effectively suppressing hydrogen sulfide generation, the difference between the two is preferably within 0.5°, and particularly preferably within 0.1°.

[0036] In order to make the solid electrolyte of the present invention satisfy the above formulas (1) and (2), it is sufficient to manufacture the solid electrolyte by, for example, the method described later.

[0037] The results of the research by the present inventors show that in the operation of separating the waveforms of diffraction peaks, peak A1, which is the main peak, is approximated by a Gaussian function, and peak A2, which is a peak derived from a crystal phase other than the thiogermanate crystal structure, is approximated by an asymmetric double S function, and a highly accurate waveform separation operation can be performed.

[0038] The Gaussian function is represented by the following formula (3). In the formula, A g is a constant corresponding to the peak intensity, x g is a constant representing the peak position, and w cg is a constant corresponding to the peak width. g is a constant corresponding to the peak width.

[0039]

[0040] The asymmetric double sigmoidal function y s is represented by the following formula (4). In the formula, A s is a constant corresponding to the peak intensity, x cs is a constant representing the peak position, w 1s is a constant corresponding to the peak width, w 2s and w 3s are constants corresponding to the peak width deviation.

[0041]

[0042] The waveform separation operation and curve fitting of the diffraction peaks can be implemented using appropriate software or the like. As an example, the least squares method using the solver function of the spreadsheet software Excel (Microsoft) can be cited.

[0043] Specifically, for the reliability factor R expressed by the following formula (5), the fitting is performed by minimizing it using the GRG non-linearity with the solver function. I(2θ) in formula (5) represents the signal intensity of the actual data. In addition, P(2θ) in formula (5) is the fitting curve. Specifically, as shown in formula (6), it is expressed as the sum of the Gaussian function y corresponding to peak A1, the asymmetric double S function y corresponding to peak A2, and the constant y0 corresponding to the baseline. g corresponding to peak A2, and the constant y0 corresponding to the baseline. s and the sum of the constant y0 corresponding to the baseline.

[0044] The range of the diffraction angle 2θ when calculating the reliability factor R can be any range including the diffraction peaks observed within the range of 2θ = 25.2 ± 1.0°. For example, it can be set to the range above 23.0° and below 27.0°.

[0045] As parameters for fitting, the constants A, x, W of the Gaussian function for peak A1 expressed by formula (3), and the constants A, x, W, W, W, W of the asymmetric double S function for peak A2 expressed by formula (4), and the baseline y0 are used. The curve fitting is judged to converge only when the R factor is 20% or less; when the R factor diverges and its value is greater than 20%, the next step is entered. g x cg W g and the constants A, x, W of the asymmetric double S function for peak A2 expressed by formula (4), s x cs W 1s W 2s W 3s and the baseline y0. The curve fitting is judged to converge only when the R factor is 20% or less; when the R factor diverges and its value is greater than 20%, the next step is entered.

[0046]

[0047] P(2θ) = y0 + y g + y s (4)

[0048] The specific waveform separation operation of the diffraction peaks is performed according to the flowchart shown as follows. Hereinafter, this flowchart will be described in detail. Figure 1 shown flowchart. Hereinafter, this flowchart will be described in detail.

[0049] First, in step 1, the parameters A, x, W of the Gaussian function for peak A1 expressed by formula (3), and the parameters A, x, W, W, W, W of the asymmetric double S function for peak A2 expressed by formula (4), g x cg W g and the parameters A, x, W of the asymmetric double S function for peak A2 expressed by formula (4), s x cs W 1s W 2s W3s Perform curve fitting using the initial values shown in this figure. When the R factor converges during curve fitting, end the analysis and determine peaks A1 and A2.

[0050] Figure 1 The definitions of the terms in [reference] are as follows.

[0051] "Actual data peak intensity" refers to the value obtained by subtracting the baseline from the height of the vertex signal of the peak with the maximum intensity among the diffraction peaks observed in the range of 2θ = 25.2 ± 1.0°.

[0052] "Actual data peak position" refers to the value of the diffraction angle 2θ at the vertex signal of the peak with the maximum intensity among the diffraction peaks observed in the range of 2θ = 25.2 ± 1.0°.

[0053] "Actual data full width at half maximum" refers to the absolute value of the difference in the diffraction angle 2θ at the signal where the intensity is 1 / 2 of the actual data peak intensity among the diffraction peaks observed in the range of 2θ = 25.2 ± 1.0°, after subtracting the baseline. It should be noted that when there are more than 3 signals at the diffraction angle 2θ where the intensity is 1 / 2 of the actual data peak intensity, take the difference between the signal closest to the high-angle side and the signal closest to the low-angle side of the actual data peak position.

[0054] "Actual data 1 / 4 height width" refers to the absolute value of the difference in the diffraction angle 2θ at the signal where the intensity is 1 / 4 of the actual data peak intensity among the diffraction peaks observed in the range of 2θ = 25.2 ± 1.0°, after subtracting the baseline. It should be noted that when there are more than 3 signals at the diffraction angle 2θ where the intensity is 1 / 4 of the actual data peak intensity, take the difference between the signal closest to the high-angle side and the signal closest to the low-angle side of the actual data peak position.

[0055] When the R factor does not converge in Step 1, proceed to Step 2, change the initial values according to the rules shown in Figure 1 and perform curve fitting again. When the R factor converges during curve fitting, end the analysis and determine peaks A1 and A2.

[0056] When the R factor does not converge in Step 2, proceed to Step 3, further change the initial values according to the rules shown in Figure 1 and perform curve fitting again. When the R factor converges during curve fitting, end the analysis and determine peaks A1 and A2.

[0057] When the R factor does not converge in Step 3 either, proceed to Step 4, according to Figure 1The rules shown further change the initial value and perform curve fitting again. When the R factor in the curve fitting converges, the analysis ends, and peaks A1 and A2 are determined. When the R factor in the curve fitting does not converge, it is determined that curve fitting based on the Gaussian function and the asymmetric double S function is not feasible, and curve fitting is performed only with the Gaussian function, and only peak A1 is determined. For peak A2, its intensity is judged to be 0.

[0058] An example of the waveform separation result obtained in this way is as Figure 2 shown. Figure 2 The result of the waveform separation operation on the diffraction peak of the solid electrolyte obtained in Example 1 is shown. As shown in this figure, diffraction peak A is separated into peak A1 approximated by the Gaussian function and peak A2 approximated by the asymmetric double S function.

[0059] Using the function y represented by peak A1 obtained by curve fitting g , the peak intensity I A1 and the full width at half maximum W A1 can be calculated. Specifically, let the highest value in the function y g be the peak intensity I A1 , and the difference between the two diffraction angles 2θ with an intensity of I A1 of 1 / 2 be the full width at half maximum W A1 . Similarly, using the function y represented by peak A2 obtained by curve fitting s , the peak intensity I A2 and the full width at half maximum W A2 can be calculated. Specifically, let the highest value in the function y s be the peak intensity I A2 , and the difference between the two diffraction angles 2θ with an intensity of I A2 of 1 / 2 be the full width at half maximum W A2 .

[0060] In the present invention, from the perspective of further achieving high lithium ion conductivity and more effectively suppressing the generation of hydrogen sulfide, it is advantageous to control the composition of the constituent elements of the solid electrolyte. Specifically, the molar ratio X / P of element X to element P is preferably set to 1.0 or more and 3.0 or less. In particular, the molar ratio of X / P is preferably set to 1.2 or more and 2.8 or less, especially 1.3 or more and 2.5 or less.

[0061] Regarding the composition of the constituent elements in the solid electrolyte, it is also advantageous to control the molar ratio of element S to element P. Specifically, the molar ratio S / P of element S to element P is preferably set to 3.0 or more and 5.0 or less. In particular, when the S / P molar ratio is set to 3.5 or more and 4.8 or less, especially 4.0 or more and 4.5 or less, the lithium ion conductivity of the solid electrolyte is further increased and the generation of hydrogen sulfide is more effectively suppressed, so it is preferred.

[0062] Furthermore, regarding the composition of the constituent elements in the solid electrolyte, the solid electrolyte contains at least Br element as the X element, which can further increase the lithium ion conductivity of the solid electrolyte and more effectively inhibit the generation of hydrogen sulfide, and is thus preferred. The proportion (mol%) of the Br element in the X element is, for example, 50% or more, more preferably 60% or more, still more preferably 70% or more, 80% or more, or even 90% or more. In addition, the proportion of the Br element can also be 100%. That is, only the Br element can be included as the X element. When the solid electrolyte contains other X elements in addition to the Br element as the X element, examples of the other X elements include, for example, chlorine (Cl) element, fluorine (F) element, and iodine (I) element, and the Cl element is particularly preferably used.

[0063] From the perspective of improving the lithium ion conductivity of the solid electrolyte, it is preferred that the solid electrolyte of the present invention is represented by the compositional formula Li a PS b X c (X is a halogen element containing at least Br element).

[0064] In the above compositional formula, a representing the molar ratio of lithium element is, for example, a number of 3.0 or more and 6.5 or less, more preferably 3.2 or more and 6.5 or less, still more preferably 3.4 or more and 6.5 or less.

[0065] In the above compositional formula, b representing the molar ratio of sulfur element is, for example, a number of 3.5 or more and 4.8 or less, more preferably 3.8 or more and 4.6 or less, still more preferably 4.0 or more and 4.6 or less.

[0066] In the above compositional formula, c is, for example, a number of 0.1 or more and 3.0 or less, more preferably 0.2 or more and 2.8 or less, still more preferably 0.4 or more and 2.5 or less.

[0067] The solid electrolyte having a composition with a, b, and c within this range has a sufficiently high lithium ion conductivity.

[0068] The solid electrolyte of the present invention may contain elements other than Li element, P element, S element, and X element. For example, a part of the Li element may be replaced with other alkali metal elements, a part of the P element may be replaced with other nitrogen group elements, and a part of the S element may be replaced with other chalcogen elements.

[0069] The solid electrolyte of the present invention is a product having lithium ion conductivity in a solid state. The solid electrolyte of the present invention preferably has a lithium ion conductivity of, for example, 0.5 mS / cm or more, more preferably 1.0 mS / cm or more, particularly preferably 1.5 mS / cm or more, and especially preferably 1.7 mS / cm or more at room temperature, i.e., 25°C. The lithium ion conductivity can be measured by the method described in the examples below.

[0070] The solid electrolyte of the present invention is preferably composed of powder which is an aggregate of particles. The particle size of the solid electrolyte of the present invention is represented by the volume median diameter D in the cumulative volume 50% by volume based on the laser diffraction scattering type particle size distribution measurement method, and is, for example, 10 μm or less, more preferably 8.0 μm or less, and especially preferably 7.0 μm or less. On the other hand, the volume median diameter D 50 is, for example, 0.1 μm or more, more preferably 0.3 μm or more, and particularly preferably 0.5 μm or more. By setting the particle size within this range, the contact points and contact area between the particles of the solid electrolyte become larger, and the improvement of lithium ion conductivity can be effectively achieved. In addition, since the specific surface area does not become too large, the generation of hydrogen sulfide can be effectively suppressed. 50

[0071] The solid electrolyte of the present invention can be advantageously manufactured by the method described below. As raw materials, a Li element source, a P element source, an S element source, and a Br element source are used. As the Li element source, for example, lithium sulfide (Li2S) can be used. As the P element source, for example, phosphorus pentasulfide (P2S5) can be used. As the S element source, when the Li element source and / or the P element source is a sulfide, the sulfide can be used as the S element source. As the Br element source, lithium bromide can be used. The raw material composition obtained by mixing these raw materials so that the Li element, the P element, the S element, and the Br element reach a specified molar ratio is pulverized. And the pulverized raw material composition is calcined in an inert gas atmosphere or in an atmosphere containing hydrogen sulfide gas.

[0072] Particularly in this manufacturing method, by controlling the particle size and crystal structure of the raw material composition, the target solid electrolyte can be smoothly manufactured. Specifically, it is advantageous to appropriately adjust the operating conditions of the media mill for mixing and pulverizing the raw material composition, suppress particle growth caused by aggregation and compounding between the raw materials, and control the particle size of the raw materials to a smaller state. In addition, it is advantageous to appropriately adjust the operating conditions of the media mill for mixing and pulverizing the raw material composition and retain the crystal structure of the raw materials themselves without generating vitreous or argyrodite-type crystal structures. As a result, the solid-phase reaction of the raw material composition can proceed unevenly in the subsequent calcination process. As a result, a solid electrolyte capable of observing peak A that can be waveform-separated into the above-mentioned peak A1 and peak A2 can be easily obtained. In addition, since excessive pulverization is not performed, the crystal grain size of the argyrodite-type crystal structure compound obtained in the subsequent calcination process can be prevented from becoming excessively large. Furthermore, excessive pulverization energy does not need to be applied in the subsequent pulverization process, so the exposure of unstable new surfaces can be suppressed and the generation of hydrogen sulfide can be inhibited.

[0073] For the mixing and pulverization of the raw material composition, it is preferable to use a media mill such as a bead mill or a ball mill. The energy applied during pulverization is preferably such that the raw material composition is pulverized but no mechanochemical reaction occurs. For example, the table speed of the media mill is preferably 500 rpm or less, more preferably 400 rpm or less, and even more preferably 300 rpm or less. In addition, the processing time of the media mill is preferably 5 minutes or more, more preferably 30 minutes or more. On the other hand, the above-mentioned processing time is preferably 15 hours or less, more preferably 12 hours or less, and even more preferably 10 hours or less.

[0074] Thus, after the mixing and pulverization of the raw material composition are completed, the raw material composition is then calcined. The calcination is preferably carried out in an inert gas atmosphere such as nitrogen or in an atmosphere containing hydrogen sulfide gas. The atmosphere containing hydrogen sulfide gas can be 100% hydrogen sulfide gas, or it can also be a mixed gas of hydrogen sulfide gas and an inert gas such as argon. Among them, an inert gas atmosphere such as nitrogen is more preferable. The reason is that a decrease in the sulfur partial pressure in the atmosphere makes it difficult for the solid-phase reaction in the raw material composition to proceed, so that an argyrodite-type crystal structure can be unevenly generated, and thus a solid electrolyte capable of observing peak A that can be waveform-separated into the above-mentioned peak A1 and peak A2 can be easily obtained. In addition, from an industrial perspective, it is also preferable to carry out the calcination in an inert gas atmosphere that is easy to operate.

[0075] The calcination temperature is preferably 350 °C or higher, more preferably 420 °C or higher, and even more preferably 470 °C or higher. On the other hand, the calcination temperature is preferably 600 °C or lower, more preferably 550 °C or lower, and even more preferably 520 °C or lower.

[0076] The firing time is preferably, for example, 0.5 hour, more preferably 2 hours or more. On the other hand, the firing time is preferably 20 hours or less, more preferably 10 hours or less, and even more preferably 5 hours or less. The reason is that a solid electrolyte containing a crystalline phase having an argyrodite crystal structure can be advantageously obtained.

[0077] The fired product thus obtained is subjected to a prescribed pulverization process. When pulverizing the fired product, either dry pulverization or wet pulverization can be carried out, or both can be combined. Due to the non-uniform solid-phase reaction, the fired product obtained by mixing, pulverizing, and firing the above raw material composition forms a complex of multiple argyrodite crystal structure compounds with different composition ratios and crystallinities. Therefore, compared with the fired product obtained by a uniform solid-phase reaction, there are more grain boundaries. In the pulverization process of the fired product, even a small amount of pulverization energy can achieve the desired particle size. As a result, according to this manufacturing method, the generation of defects in the argyrodite crystal structure can be suppressed. As a result, the reactivity with moisture is suppressed, and solid electrolyte particles with less hydrogen sulfide generation can be easily obtained. In addition, according to this manufacturing method, since there are many grain boundaries in the fired product, the proportion of newly formed surfaces with high reactivity exposed in the pulverization process can be reduced, and thus the generation of hydrogen sulfide can also be suppressed from this perspective.

[0078] From the perspective of causing the above non-uniform solid-phase reaction, as the X element constituting the solid electrolyte, compared with the Cl element whose raw material has a high melting point and requires a large amount of thermal energy for solid-phase reaction, it is more preferable to use the Br element or I element whose raw materials have a relatively low melting point and can cause solid-phase reaction even with a small amount of thermal energy.

[0079] On the other hand, from the perspective of improving the ionic conductivity of the solid electrolyte containing a crystalline phase having an argyrodite crystal structure, it is more preferable to use the Cl element or Br element.

[0080] Taking the above factors into account, in order to fully exert the effects of the present invention, as the X element constituting the solid electrolyte, it is particularly preferable to use the Br element alone or to use the two elements of the Br element and the Cl element.

[0081] The solid electrolyte obtained by the above method can be used as a material for forming a solid electrolyte layer, a positive electrode layer, or a negative electrode layer. Specifically, the solid electrolyte of the present invention can be used in a battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer. That is, the solid electrolyte can be used in a so-called solid-state battery. More specifically, it can be used in a lithium solid-state battery. The lithium solid-state battery can be a primary battery or a secondary battery. The shape of the battery is not particularly limited, and shapes such as a laminate type, a cylindrical type, and a square type can be adopted. The "solid-state battery" includes not only a solid-state battery that contains no liquid substance or gel-like substance at all as an electrolyte, but also a form that contains, for example, 50% by mass or less, 30% by mass or less, 10% by mass or less of a liquid substance or a gel-like substance as an electrolyte.

[0082] When the solid electrolyte layer contains the solid electrolyte of the present invention, the solid electrolyte layer can be manufactured by, for example, the following methods: a method of dropping a slurry composed of a solid electrolyte, a binder, and a solvent onto a substrate and leveling it with a doctor blade or the like; a method of cutting with an air knife after bringing the substrate into contact with the slurry; a method of forming a coating film by a screen printing method or the like and then removing the solvent by heating and drying. Or it can also be manufactured by appropriately processing a compact obtained by pressing a powdery solid electrolyte.

[0083] In consideration of the balance between preventing short circuits and volume capacity density, the thickness of the solid electrolyte layer is typically preferably 5 μm or more and 300 μm or less, and more preferably 10 μm or more and 100 μm or less.

[0084] The solid electrolyte of the present invention can be used together with an active material to form an electrode mixture. The proportion of the solid electrolyte in the electrode mixture is typically 10% by mass or more and 50% by mass or less. The electrode mixture can contain other materials such as a conductive auxiliary agent and a binder as needed. An electrode layer such as a positive electrode layer and / or a negative electrode layer can be produced by mixing the electrode mixture with a solvent to make a paste, and then coating and drying it on a current collector such as an aluminum foil.

[0085] As the positive electrode material constituting the positive electrode layer, a positive electrode material used as a positive electrode active material for a lithium ion battery can be appropriately used. For example, a lithium-containing positive electrode active material, specifically, spinel-type lithium transition metal oxides and layered-structured lithium metal oxides can be cited. By using a high-voltage type positive electrode material as the positive electrode material, an improvement in energy density can be achieved. In addition to the positive electrode active material, the positive electrode material can contain a conductive material or other materials.

[0086] As the negative electrode material constituting the negative electrode layer, a negative electrode material used as a negative electrode active material for a lithium ion battery can be appropriately used. Since the solid electrolyte of the present invention is electrochemically stable, a material that can be charged and discharged under the condition of lithium metal or a low potential equivalent to lithium metal (about 0.1V vs Li + / Li) can be used as the negative electrode material, that is, carbon-based materials such as graphite, artificial graphite, natural graphite, and non-graphitizable carbon (hard carbon) can be used as the negative electrode material. Thereby, the energy density of the solid state battery can be greatly improved. In addition, silicon or tin, which is expected to be a high-capacity material, can also be used as the active material. In a battery using a conventional electrolyte, the electrolyte reacts with the active material during charge and discharge, and the deterioration of battery characteristics is significant due to the corrosion of the active material surface. In contrast, when the solid electrolyte of the present invention is used instead of the electrolyte and silicon or tin is used as the negative electrode active material, since the above corrosion reaction does not occur, the durability of the battery can be improved. The negative electrode material may also contain a conductive material in addition to the negative electrode active material, or may contain other materials.

[0087] Examples

[0088] The present invention will be described in more detail below by way of examples. However, the scope of the present invention is not limited to these examples.

[0089] 〔Example 1〕

[0090] In order to achieve the composition shown in Table 1 below, Li2S powder, P2S5 powder, and LiBr powder were weighed. These powders were pulverized and mixed using a planetary ball mill (P-5 manufactured by Fritsch) to obtain a raw material composition. The obtained raw material composition was calcined to obtain a calcined product. The calcination was carried out using a tubular electric furnace. During the calcination, nitrogen gas was introduced into the electric furnace. The calcination temperature was set at 500 °C and calcination was carried out for 4 hours. The calcined product was pulverized using a ball mill to obtain a powder of the target solid electrolyte. It was confirmed by the results of XRD measurement that this powder was a crystalline phase having a thioargentogermanite-type crystal structure.

[0091] 〔Examples 2 to 4〕

[0092] Except that the raw material composition was prepared in such a way as to achieve the composition shown in Table 1 below, the same operations as in Example 1 were carried out to obtain a powder of the solid electrolyte. It was confirmed that this powder was a crystalline phase having a thioargentogermanite-type crystal structure.

[0093] 〔Comparative Examples 1 to 3〕

[0094] Prepare each raw material powder in such a way as to achieve the composition shown in Table 1 below. In addition, as shown in this table, crush the raw material composition under the conditions that the rotational speed of the planetary ball mill is higher than that of the example and the time is longer than that of the example. And as shown in this table, bake the raw material composition under the conditions that the temperature is lower than that of the example and the duration is longer. In addition to this, perform the same operations as in Example 1 to obtain the powder of the solid electrolyte.

[0095] 〔XRD measurement〕

[0096] For the solid electrolytes obtained in the examples and comparative examples, perform XRD measurement under the following conditions, and perform the waveform separation operation of the diffraction peak according to the flowchart as Figure 1 shown. And for the peaks A1 and A2 obtained by the waveform separation operation, find the peak position, I A2 / I A1 and W A2 / W A1 . Show the results in Table 1. In addition, Figure 2 shows the result of the waveform separation operation of the diffraction peak of the solid electrolyte obtained in Example 1.

[0097] The XRD measurement is carried out using the X-ray diffractometer "Smart Lab" manufactured by Rigaku Corporation. The measurement conditions are non-exposure to air, scanning axis: 2θ / θ, scanning range: 10° or more and 120° or less, step size 0.02°, scanning speed 1° / min. The X-ray source is CuKα1 ray using a Johann-type crystal. Detection uses a one-dimensional detector. The measurement is carried out in such a way that the intensity at 21.3 ± 1.0° reaches a count value of 100 or more and 700 or less. In addition, it is carried out in such a way that the maximum peak intensity in the range of 10° or more and 120° or less reaches a count value of 1000 or more.

[0098] 〔Lithium ion conductivity〕

[0099] For the solid electrolytes obtained in the examples and comparative examples, measure the lithium ion conductivity by the following method. The results are shown in Table 1 below.

[0100] Inside a glove box replaced with sufficiently dried argon (dew point -60°C or lower), apply a uniaxial pressure of about 6 t / cm 2 to each solid electrolyte to form a sample for measuring lithium ion conductivity composed of pellets with a diameter of 10 mm and a thickness of about 1 mm to 8 mm. The measurement of lithium ion conductivity is carried out using Solartron 1255B manufactured by Toyo Technica Corporation. The measurement conditions are an alternating current impedance method at a temperature of 25°C, a frequency of 100 Hz to 1 MHz, and an amplitude of 100 mV.

[0101] 〔Amount of hydrogen sulfide generated〕

[0102] For the solid electrolytes obtained in the examples and comparative examples, the amount of hydrogen sulfide generated was measured by the following method. The results are shown in Table 1 below.

[0103] In a glove box purged with sufficiently dry argon (dew point below -60°C), 2 mg of each solid electrolyte was weighed and placed in a bag sealed with a laminated film. Then, in an atmosphere with a dew point of -30°C adjusted by mixing dry air and the atmosphere, a separable glass flask with a volume of 1500 cm 3 was placed in a thermo-hygrostat maintained at room temperature (25°C). The separable flask was kept until the inside reached the same environment as that in the thermo-hygrostat, and then the sealed bag containing the solid electrolyte was opened in the thermo-hygrostat, and the solid electrolyte was quickly placed into the separable flask. A fan was provided in the separable flask for the purpose of suppressing gas retention, and the fan was rotated to stir the atmosphere in the separable flask. After 30 minutes, the concentration of hydrogen sulfide generated 30 minutes after sealing the separable flask was measured using a hydrogen sulfide detector (GX-2009 manufactured by Riken Keiki Co., Ltd.). The minimum measurable value of the hydrogen sulfide detector is 0.1 ppm.

[0104] [Table 1]

[0105]

[0106] From the results shown in Table 1, it can be seen that the solid electrolytes obtained in each example have a higher lithium ion conductivity and suppress the generation of hydrogen sulfide compared to the solid electrolytes of the comparative examples.

[0107] Industrial Applicability

[0108] According to the present invention, a solid electrolyte capable of suppressing the generation of hydrogen sulfide can be provided.

Claims

1. A solid electrolyte comprising lithium (Li), phosphorus (P), sulfur (S) and halogen (X) elements, wherein the halogen (X) element contains at least bromine (Br) element, the solid electrolyte contains a crystalline phase having a thiogermanate-type crystal structure, in the X-ray diffraction pattern measured by an X-ray diffraction apparatus (XRD) using CuKα1 as the radiation source, there is a peak A in the range of 2θ = 25.2 ± 1.0°, The peak A is separated into two peaks, namely peak A1 and peak A2, through waveform separation operation. Among them, peak A1 is approximated by a Gaussian function, and peak A2 is approximated by an asymmetric double-S function. Let the intensity of the peak A1 be I A1 and the intensity of the peak A2 be I A2 . When the I A2 relative to the I A1 ratio (I A2 / I A1 ) is 0.37 or more Let the full width at half maximum of peak A1 be W A1 and the full width at half maximum of peak A2 be W A2 When this is the case, the ratio of this W A2 relative to this W A1 (W A2 / W A1 ) is 3.2 or more.

2. The solid electrolyte according to claim 1, wherein the molar ratio of the bromine (Br) element to the halogen (X) element (Br / X) is 0.5 or more.

3. The solid electrolyte according to claim 1 or 2, wherein the molar ratio of the halogen (X) element to the phosphorus (P) element (X / P) is 1.0 or more and 3.0 or less, the molar ratio of the sulfur (S) element to the phosphorus (P) element (S / P) is 3.0 or more and 5.0 or less.

4. The solid electrolyte according to claim 1 or 2, wherein, The said I A2 Relative to the said I A1 The ratio (I A2 / I A1 ) is 1.40 or less.

5. The solid electrolyte according to claim 1 or 2, wherein, The said W A2 relative to the said W A1 The ratio (W A2 / W A1 ) is 15.0 or less.

6. An electrode mixture comprising the solid electrolyte according to any one of claims 1 to 5 and an active material.

7. A solid electrolyte layer containing the solid electrolyte according to any one of claims 1 to 5.

8. A battery having a positive electrode layer, a negative electrode layer and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, the battery containing the solid electrolyte according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Solid electrolyte for all-solid lithium secondary battery, all-solid lithium secondary battery, and method of preparing the solid electrolyte

    US20190148769A1

  • Sulfide solid electrolyte and battery

    WO2020095936A1